Enhancing Student Engagement: A Toolbox for Systematic PBL Implementation - Yuan, Meng; Chen, Juebei; Friedrichsen, Dennis; Jiskani, Izhar Mithal; Aaen, Sara Bjørn; Du, Xiangyun (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
To foster student engagement and improve learning outcomes, there is a growing shift from traditional teacher-centered, lecture-based teaching to student-centered, constructivist approaches. This paper proposes a student engagement toolbox designed to promote active student engagement in a systematic problem-based learning environment. The toolbox includes tools that support diverse teaching contexts, such as the 1-2-Team model, digital interaction tools, teamwork on cases, random interviews, and flipped classroom activities. To offer deeper insights, an example of applying the elements of the toolbox in a specific course at Aalborg University is presented. Furthermore, the practical implications of the toolbox are discussed, including application scenarios, advantages, potential risks, strategies for mitigating those risks, and authors’ reflections on its implementation. The findings highlight the importance of selecting tools and designing courses according to the teaching contexts to promote psychological safety and foster student interactions. This approach ultimately contributes to an improved learning experience by creating an inclusive and supportive atmosphere, empowering students to take an active role in their education.